CROP INSURANCE – RISKS AND MODELS OF INSURANCE - Čolović, Vladimir; Mrvić Petrović, Nataša (Economics of Agriculture, 2014)
The issue of crop protection is very important because of a variety of risks that could cause diffcult consequences. One type of risk protection is insurance. The author in the paper states various models of insurance in some EU countries and the systems of subsidizing of insurance premiums by state. The author also gives a picture of crop insurance in the U.S., noting that in this country pays great attention to this matter. As for crop insurance in Serbia, it is not at a high level. The main problem with crop insurance is not only the risks but also the way of protection through insurance. The basic question that arises not only in the EU is the question is who will insure and protect crops. There are three possibilities: insurance companies under state control, insurance companies that are public-private partnerships or private insurance companies on a purely commercial basis.